2003
DOI: 10.1073/pnas.0337418100
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of the T cell antitumor response by positron-emission tomography

Abstract: We describe a noninvasive, quantitative, and tomographic method to visualize lymphocytes within the whole animal. We used positron-emission tomography (PET) to follow the localization of adoptively transferred immune T lymphocytes. Splenic T cells from animals that had rejected a Moloney murine sarcoma virus͞ Moloney murine leukemia virus (M-MSV͞M-MuLV)-induced tumor were marked with a PET reporter gene, injected into tumor-bearing mice, and imaged in a microPET by using a substrate specific for the reporter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 38 publications
1
93
0
Order By: Relevance
“…We use the term ''tracer cells'' in context of the potential future clinical scenario, in which the HSV1-TK-expressing hMSCs will be used to ''trace'' the coadministered therapeutic hMSCs genetically modified to express various anticancer cytokines (12,13). Similar PET imaging approach was applied in several recent studies for noninvasively visualization of HSV1-TK-expressing stem cells after direct intramyocardial injection (30,31) and for visualization of tumor targeting by the adoptively transferred tumor antigen-specific T cells (32,33). Another potential clinical therapeutic protocol, which would be greatly facilitated by noninvasive imaging, would include repetitive (e.g., biweekly or monthly) administration of HSV1-TK-expressing autologous stem cells to patients following resection of a primary tumor, which has high likelihood of metastases that are radiologically not detectable at the time of resection.…”
Section: Discussionmentioning
confidence: 99%
“…We use the term ''tracer cells'' in context of the potential future clinical scenario, in which the HSV1-TK-expressing hMSCs will be used to ''trace'' the coadministered therapeutic hMSCs genetically modified to express various anticancer cytokines (12,13). Similar PET imaging approach was applied in several recent studies for noninvasively visualization of HSV1-TK-expressing stem cells after direct intramyocardial injection (30,31) and for visualization of tumor targeting by the adoptively transferred tumor antigen-specific T cells (32,33). Another potential clinical therapeutic protocol, which would be greatly facilitated by noninvasive imaging, would include repetitive (e.g., biweekly or monthly) administration of HSV1-TK-expressing autologous stem cells to patients following resection of a primary tumor, which has high likelihood of metastases that are radiologically not detectable at the time of resection.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported that the localization of tumorspecific T cells at the tumor site is often a requirement for regression of systemic tumors (42) and even CNS tumors (43). In this clinical trial, we also observed dramatic intratumoral infiltration of CD8 + and CD4 + CTL in some patients following dendritic cell vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the in vivo dynamics of the infused cells and how they specifically target tumors would provide information about potential problems, such as lack of specific tumor homing following ex vivo expansion, inappropriate sequestration in nonantigen positive sites, or rapid cell death and inability for the adoptively transferred TCR transgenic cells to persist in vivo. The study of these possibilities can be achieved with modern molecular imaging techniques with reporter gene labeling of cells to allow noninvasive detection of adoptively transferred TCR transgenic cell populations in recipients (8). In the current work we have taken the molecular imaging gene marking approach of antigen-specific T cells one step closer to the clinic by simultaneously redirecting the TCR specificity of T cells and providing genetic labeling for molecular imaging demonstrating robust antitumor activity correlated with specific tumor targeting.…”
mentioning
confidence: 99%